Postcolonial Life Narratives: Testimonial Transactions, by Gillian Whitlock - Dawes, James (Refuge: Canada’s Journal on Refugees, 2015)
Postcolonial Life Narratives: Testimonial Transactions by Gillian Whitlock Oxford: Oxford University Press, 2015, pp. 242